Understanding the Rate Capability of High‐Energy‐Density Li‐Rich Layered Li1.2Ni0.15Co0.1Mn0.55O2 Cathode Materials. Issue 5 (23rd December 2013) - Yu, Xiqian; Lyu, Yingchun; Gu, Lin; Wu, Huiming; Bak, Seong‐Min; Zhou, Yongning; Amine, Khalil; Ehrlich, Steven N.; Li, Hong; Nam, Kyung‐Wan; Yang, Xiao‐Qing
<x xml:space="preserve">Abstract</x> The high‐energy‐density, Li‐rich layered materials, i.e., xLiMO2(1‐x)Li2MnO3, are promising candidate cathode materials for electric energy storage in plug‐in hybrid electric vehicles (PHEVs) and electric vehicles (EVs). The relatively low rate capability is one of the major problems that need to be resolved for these materials. To gain insight into the key factors that limit the rate capability, in situ X‐ray absorption spectroscopy (XAS) and X‐ray diffraction (XRD) studies of the cathode material, Li1.2Ni0.15Co0.1Mn0.55O2 [0.5Li(Ni0.375Co0.25 Mn0.375)O2·0.5Li2MnO3], are carried out. The partial capacity contributed by different structural components and transition metal elements is elucidated and correlated with local structure changes. The characteristic reaction kinetics for each element are identified using a novel time‐resolved XAS technique. Direct experimental evidence is obtained showing that Mn sites have much poorer reaction kinetics both before and after the initial activation of Li2MnO3, compared to Ni and Co. These results indicate that Li2MnO3 may be the key component that limits the rate capability of Li‐rich layered materials and provide guidance for designing Li‐rich layered materials with the desired balance of energy density and rate capability for different applications.